2015
DOI: 10.1016/j.cities.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Chittagong, Bangladesh

Abstract: a b s t r a c tLocated in the southeast, metropolitan Chittagong is the second largest city in Bangladesh. Its strategic location as the busiest seaport in the region has made it a major economic hub attracting strong inflows of foreign investment into the production of apparel, ship breaking and oil refinery activities. The city boasts a deep harbor that supports strongly commerce, business and industrial activities. However, despite its rich scenic and natural endowments, population growth and poor planning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…KR estuary is located in the city of Chittagong which is experiencing rapid and frequent economic development activities (Mia et al 2015), and human activities reported to collide with nature that eventually affecting the estuarine environment and ecosystems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KR estuary is located in the city of Chittagong which is experiencing rapid and frequent economic development activities (Mia et al 2015), and human activities reported to collide with nature that eventually affecting the estuarine environment and ecosystems.…”
Section: Resultsmentioning
confidence: 99%
“…Originating from various anthropogenic and natural sources, metals are eventually released into aquatic or atmospheric systems, although the anthropogenic inputs in environments have increased dramatically since the Industrial Revolution (Nriagu 1979; Thevenon et al 2011). Bangladesh being a developing country is experiencing rapid industrial developments and unplanned urban growth in recent years (Mia et al 2015), but pollutants produced by these activities are triggering environmental problems on an unprecedented scale, primarily due to arsenic and other heavy metal pollution (Tareq et al 2003; Bhuiyan et al 2011; Islam et al 2015a; Sharifuzzaman et al 2016). For example, the aquatic ecosystems of Chittagong, which is a second largest city, main seaport and economic nerve-centre of the country, is under multiple stresses due to discharge of effluents from textile and cement industries, ship recycling, oil refineries, tanneries, paint manufacturing and dyeing plants, paper and rayon mills, naval and merchant ships, steel and engineering factories, fertilizer and other chemical industries as well as disposal of sewage and solid wastes directly into the adjacent Karnaphuli River (KR) and coastal waters of Bay of Bengal (Chowdhury et al 1999; Hossain and Khan 2002; Ali et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The people inhabiting this area are mainly involved in the primary activities (e.g., farming, fishing) for sustenance, which make them vulnerable to any adverse environmental processes [5]. In the past, people have migrated away from this region due to cyclones, storm surges and other natural disasters [46] that account for the stunted development of the region [47,48]. The high population density in this region has also led to the exploitation of the newly formed islands (locally known as Chars), an issue which also strongly contributes to LULC changes along the coastal areas of Bangladesh [39].…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…This net migration is explained in large part by internal migration to the two major urban centres of the country, Dhaka and Chattogram, where employment and access to services are offered in higher proportion compared to rural areas. Dhaka had net annual migration arrivals between 2000 and 2010 of 300-400,000 (te Lintelo et al 2018), while Chattogram had an aggregate population of 3.3 million in 2001 and four million in 2011 with an annual growth rate of 3.6% between 1990 and 2011 (Mia et al 2015). The majority of new arrivals to Chattogram are associated with economic opportunities brought about by rapid industrialisation such as garment manufacture (which is responsible for two-thirds of the growth in employment in Chattogram [Mia et al 2015]).…”
Section: Spatial Variation In Population Driven By Migration Processesmentioning
confidence: 99%
“…Dhaka had net annual migration arrivals between 2000 and 2010 of 300-400,000 (te Lintelo et al 2018), while Chattogram had an aggregate population of 3.3 million in 2001 and four million in 2011 with an annual growth rate of 3.6% between 1990 and 2011 (Mia et al 2015). The majority of new arrivals to Chattogram are associated with economic opportunities brought about by rapid industrialisation such as garment manufacture (which is responsible for two-thirds of the growth in employment in Chattogram [Mia et al 2015]). The Volta Delta also has a negative net migration of about 41,000 people over the period 2000-2010, representing 4.8% of the mid-year population of the area in 2010.…”
Section: Spatial Variation In Population Driven By Migration Processesmentioning
confidence: 99%